Increasing self-regulated learning of elementary school students through the concrete-pictorial-abstract approach during the COVID-19 pandemic - Hafiziani Eka Putri; Idat Muqodas; Ayu Shandra Sasqia; Afif Abdulloh; Aan Yuliyanto (Universitas PGRI Madiun, 2020)
This research was motivated by limited self-regulated learning (SRL) in elementary school students. The aim of this research was to understand the increase in SRL of elementary school students apply the Concrete-Pictorial-Abstract (CPA) approach which was reviewed as a whole and based on Early Mathematical Ability (EMA) during the COVID-19. This study was applied with a quasi-experimental method through a nonequivalent control group. Determination of the sample through purposive sampling on fifth-grade elementary school students in Central Jakarta. The sample coincide of 27 students each for the CPA and the conventional class. Measurement through a scale of SRL. This research informs the students' SRL on CPA learning that is significantly better than SRL with conventional approach reviewed as a whole and in the medium EMA group., however, based on the high and low EMA groups, SRL students who received CPA learning were not significantly better than those with conventional learning.